Tax policy in the digital economy and its effect on the mechanism of indirect taxes - Jalilov Rahmonkul Hamidovich (THE INNOVATION ECONOMY, 2026)
This article examines the impact of tax policies implemented in the tax sector in the context of the digital economy on the mechanisms for accounting for indirect taxes in the tax system.